THE EFFECT OF MARKETING MIXED STRATEGY ON MARKETING PERFORMANCE AND COMPETITIVE EXCELLENCE IN SHOPPING MALL IN BADUNG AND DENPASAR REGENCY - Zen Zen Guisi (Universitas Warmadewa, 2018)
The objective of this study is to identify the effect of marketing mixed strategy on marketing performance and competitive excellence at shopping mall in Badung and Denpasar. The data were collected by distributing questionnaires to 43 respondents taken by slovin formula method. Respondents were managers and leaders of shopping malls in Badung and Denpasar regencies. Data were analyzed by Partial Least Square (PLS) analysis method. Measurement of research variables is done by using Likert scale to test the research instrument with validity and reliability test. The results showed that to achieve marketing performance can be made through the use of 7P marketing mixed strategy aimed at achieving marketing performance with the elements of product, place, price, promotion, process, people and physical. While marketing performance has a positive and significant impact on competitive advantage, where to achieve marketing performance with elements of sales growth, customer growth and sales volume. Furthermore marketing mixed strategy has a positive effect on competitive advantage but not significant. Suggestions for further research, it needs more concern to analyze the shopping mall in Bali so that the scope becomes wider for generalization in a wider area.